2020
DOI: 10.3389/frobt.2020.608841
|View full text |Cite
|
Sign up to set email alerts
|

A Soft Five-Fingered Hand Actuated by Shape Memory Alloy Wires: Design, Manufacturing, and Evaluation

Abstract: This work presents a novel five-fingered soft hand prototype actuated by Shape Memory Alloy (SMA) wires. The use of thin (100 μm diameter) SMA wire actuators, in conjunction with an entirely 3D printed hand skeleton, guarantees an overall lightweight and flexible structure capable of silent motion. To enable high forces with sufficiently high actuation speed at each fingertip, bundles of welded actuated SMA wires are used. In order to increase the compliance of each finger, flexible joints from superelastic SM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 35 publications
(70 reference statements)
0
13
0
Order By: Relevance
“…This SMA actuator concept is, therefore, different from a standard antagonistic SMA system, in which two wires are working directly against each other. [32][33][34][35][36] An example of an injection molding process with a built-in valve is shown in Figure 5, explaining the patented operating principle in a more detailed way. [37] On the left-hand side, a simplified injection mold cavity with a drilled valve seat is shown.…”
Section: Sma Actuator Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…This SMA actuator concept is, therefore, different from a standard antagonistic SMA system, in which two wires are working directly against each other. [32][33][34][35][36] An example of an injection molding process with a built-in valve is shown in Figure 5, explaining the patented operating principle in a more detailed way. [37] On the left-hand side, a simplified injection mold cavity with a drilled valve seat is shown.…”
Section: Sma Actuator Conceptmentioning
confidence: 99%
“…This SMA actuator concept is, therefore, different from a standard antagonistic SMA system, in which two wires are working directly against each other. [ 32–36 ]…”
Section: Sma Actuator Conceptmentioning
confidence: 99%
“…The surface was laser polished to allow for the least possibility for binding or friction with the used wires [ Figure 1 ]. [ 6 7 ] The sliding door has an eyelet on top to facilitate opening and closure by dental explorer [ Figure 2 ].…”
Section: Materials and Designingmentioning
confidence: 99%
“…Relevant information is provided in refs. [38][39][40][41][42][43][44][45][46] for a robotic hand or finger design, but one of the first usage of coiled shape memory alloy (SMA) muscles in a robotic finger via antagonistic pairs occurred in an earlier work in 1989. Bergamasco et al demonstrated coiled SMA muscles (0.45 mm wire diameter, 1.5 mm spring diameter, 14 coils and length of 6.3 mm) capable of lifting 3.5 N load a height of 10 mm at 0.11 Hz [45].…”
Section: Literature Reviewmentioning
confidence: 99%